About one characteristic initial value problem - Marinets, V.V.; Dobryden, A.V. (Нелінійні коливання, 2001)
The characteristic initial value problem has been studied for the second order nonlinear differential equation, and modifications of the two-sided method of its approximate integration have been constructed.